Many roads lead to Rome - Developmental paths to Olympic gold in men's field hockey - Güllich, A. (European Journal of Sport Science, 2014)
This study examined the developmental sporting activities of the Olympic Champions 2012 in men`s field hockey. The volume of organised practice/training and non-organised sporting leisure play in both field hockey and other sports through childhood, adolescence and adulthood was examined and compared between the Olympic Champions and (1) current national class players and (2) international medallists of one decade earlier. Analyses revealed that the Olympic Champions performed moderate volumes of organised field hockey practice/training throughout their career and attained their first international senior medal after accumulating 4393 ± 1389 practice/training hours, but they engaged in extensive other sporting activities during childhood and youth. It took them 18 ± 3 years of involvement to attain an international medal and they had engaged for 22 ± 3 years when winning the Olympic gold medal. The Olympic Champions did not differ from national class players in the amount of hockey-specific practice/training, but in greater amounts of organised involvement in other sports and later specialisation. They differed from the international medallists of one decade earlier in less increase of organised hockey-specific practice/training during adulthood and a longer period of involvement until attaining their first international medal. The sporting activities were characterised by sizeable interindividual variation within each subsample. The findings are reflected against the deliberate practice and Developmental Model of Sports Participation (DMSP) frameworks and are discussed with reference to the concept of long-term sustainability.